(untitled) (Communication & Society, 2024)
Various studies have analysed the news media’s participation in debates generated in the public digital sphere represented by social media, particularly X (formerly Twitter) and Instagram. Some of these debates have gained strength and become authentic movements linked to certain social struggles, such as feminism. Similarly, the so-called ‘environmental hashtivism’ or ‘eco-hashtivism’ is acquiring increasing importance in the context of this digital sphere. In view of this, the focus of this article is the distinctive area of public radio and television channels in Europe to examine the transmedia action #EKIN_klima, developed by the Basque public audiovisual corporation Euskal Irrati Telebista (EITB). The study of this pioneering initiative allows us to understand just how the eco-activism actions of the public news media can help to reposition it within the hybrid media system and contribute to the modernisation of its social function, along the lines of other actions, such as those carried out by the BBC against disinformation. In this way, it has been noted that the environmental issue is not only something to be included in the news media agenda, but also an opportunity for the public news media to legitimise its social and innovative character through transmedia branding actions.